Surveillance of Viral Respiratory Infections within Maximum-Security Prison, Australia - Nicolas M. Legrand; Rowena A. Bull; Behzad Hajarizadeh; Andrew R. Lloyd; Kirsty Johnston; Katya Issa; Christine Harvey; Alicia Arnott; Dominic E. Dwyer; Vitali Sintchenko; Luke Grant; Gregory J. Dore; et al. (Emerging Infectious Diseases)
Limited surveillance data have hindered understanding of SARS-CoV-2 transmission within prisons. We integrated routine surveillance data with viral sequencing to investigate transmission dynamics and associated factors during a Delta variant outbreak in a maximum-security prison in Sydney, New South Wales, Australia. Infection incidence and associated factors were determined by using person-time and Cox regression. We generated transmission chains by integrating epidemiologic and viral sequencing data. Of 1,562 patients, SARS-CoV-2 infection was diagnosed in 169 (11%), predominantly acquired in prison and asymptomatic. Prisonwide testing identified substantial unrecognized transmission, and 4 subvariants indicated multiple viral introductions. Infection was associated with housing location, having a cellmate (regardless of infection status), and vaccination status. Our findings underscore the inadequacy of symptom-based testing and the efficacy of entry-quarantine, strategic housing, extensive testing, and vaccination in reducing transmission. This integrated approach to surveillance and genomic sequencing offers a valuable model for enhancing infectious disease surveillance in correctional settings.